HUBUNGAN ANTARA PENGETAHUAN TENTANG SUMBER DAYA AIR DAN SIKAP TERHADAP PENGGUNAAN AIR DENGAN PERILAKU DALAM MEMANFAATKAN AIR (Studi Pada Masyarakat di Desa Linggasirna Kecamatan Sariwangi Kabupaten Tasikmalaya) - Gugum Gumilar; Yoni Hermawan (Environmental Research Center (PPLH) of Udayana University, 2017)
The study concluded that: (1) there is a relationship between people’s knowledge about the behavior of water resources in the use of water r = 0,415 and r = 17,2 %. The higher people’s knowledge about water resources, the use of positive behavior in the water anyway, (2) there is a positive relationship between attitude towards water use behavior in the use of water in the Village District Linggasirna Sariwangi Tasikmalaya district r = 0,396 and r 2 = 15,7%. The more positive attitudes towards the use of water, the use of positive behavior in the water anyway, and (3) there is a relationship between people’s knowledge about water resources and public attitudes towards water use behavior in the use of water r = 0,454 and r 2 2 = 20,6%. The higher people’s knowledge about water resources and increasingly positive attitude toward the use of water, the use of positive behavior in the water anyway.